Controlling the Decoration of the Reduced Graphene Oxide Surface with Pyrene‐Functionalized Gold Nanoparticles. Issue 11 (25th September 2017) - Gabrielli, Luca; Altoè, Giulia; Glaeske, Mareen; Juergensen, Sabrina; Reich, Stephanie; Setaro, Antonio; Menna, Enzo; Mancin, Fabrizio; Gatti, Teresa
Abstract : We exploited a non‐covalent approach based on π‐stacking interactions to address the formation of hybrids between pyrene‐functionalized gold nanoparticles (PyAuNPs) and reduced graphene oxide (RGO), in which the former are distributed homogeneously on the surface of the latter with a high degree of coverage. We used water soluble PyAuNPs of two different average dimensions, namely 2 and 8 nm, in which the pendant pyrene moieties were introduced within a mixed monolayer with a choline derivative. The combination with RGO originates highly insoluble materials, in which microscopy evidences a complete adhesion of the PyAuNPs onto the carbon nanomaterial layers in a highly homogeneous fashion, with no traces of free particles, confirming the high affinity between pyrene‐functionalized species and conjugated carbon nanostructure surfaces. Abstract : Gold nanoparticles bearing pyrene pendant groups (PyAuNPs) are employed for the preparation of functional nanohybrids with reduced graphene oxide (RGO), exploiting the formation of non‐covalent interactions between pyrene moieties and the extended π‐conjugated system of the carbon nanomaterial. A very homogeneous distribution of PyAuNPs on single RGO sheets is achieved through this approach, paving the way for the construction of suitable nano‐platforms for surface‐enhanced Raman scattering.